PESTRE-ROIRE MATRIX -A TOOL FOR DIAGNOSING FINANCIAL PERFORMANCE - Mihaela GÂDOIU; Mariana BĂNUȚĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This article aims to highlight the importance of the Pestre-Roire Matrix in diagnosing the performance of economic entities. This instrument of financial diagnosis starts from the structuring of the items in the profit and loss account by type of activities and goes through each step necessary for the construction of the final result, namely the net profit or loss of the financial year. The structural analysis of the results is carried out by grouping incomes and expenses, highlighting the use of material, financial and human resources in the activity of the entity.